Like a fish needs a bicycle - Stibbs, Anne (Bloomsbury, 1992)
A collection of over 3000 quotations by and about women, which reflect the position of women throughout the centuries. The collection is arranged under topics, and includes over 200 biographical entries on notable women and a section showing how the view of women has changed or stayed the same.